Identifying Masked Hypertension in Young Adults: A Pilot Study (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Current hypertension guidelines recommend combining both the office (clinic) BP and out-of-office (home) BP to diagnose hypertension. This study was designed to explore masked hypertension in the young adult population of a defined community by home blood pressure monitoring (HBPM).Methodology: It was a community-based, prospective, observational study conducted by the hypertension study group, Chattagram International Medical College at Ward number 4 (Chandgaon), Chattogram City Corporation, Chattogram from May 15, 2023, to September 14, 2023. Young adults of 18 to 35 years with no history of hypertension, not on any antihypertensive, with clinic BP measurement 30 years, high BMI (>25 Kg/m2), high clinic BP, sedentary lifestyle, diabetes mellitus, positive family history and smoking.Conclusion: This study emphasizes home blood pressure monitoring for identifying masked hypertension in selected cases; future research is recommended to develop optimal screening strategies.J Bangladesh Coll Phys Surg 2025; 43: 190-196